Pengaruh Fraksi Berat Serbuk Alumina Terhadap Porositas Busa Aluminium Hasil Injeksi Gas - Yulianto, Edy (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2021)
Aluminum foam is a very interesting material to develop. This material is a material that has a combination of characteristics between physical and mechanical properties such as high stiffness and low density. There are several processes for making aluminum foam that have been developed, either through the liquid, solid, or gas phases. And of these various processes, the process of making aluminum foam through the liquid phase by using the gas injection method is the simplest and cheapest process. The principle of the process of making aluminum foam with this method is that bubbles are produced from the process of blowing the gas into the aluminum liquid in which there are additive particles that function as a bubble stabilizer. These stable bubbles will become pores after the aluminum liquid solidifies. This research will discuss the effect of the weight fraction of alumina powder with an average size of 5.77 μm added to liquid aluminum on the macro-pore structure in the form of shape and size as well as the spread of the resulting pores. And the result is that the optimal weight fraction of adding alumina powder is 15%, where the resulting pores have a more homogeneous and evenly shaped and sized.